Rare case of bilateral vassal agenesis and AZFc microdeletion: A case report - Sadighi Gilani, Mohammad Ali; Sajadi, Hesamoddin (Archives of Men's Health, 2018)
Introduction: Bilateral vassal agenesis (CBAVD) is a rare cause of male infertility. Also one of the nonobstructive cause of azoospermia and infertility in men is microdeletion in long arm of Y chromosome. In this case report we have reported a rare case of CBAVD, LT renal agenesis and AZFc microdeletion. Patient Information: 28 years old man, who was farmer with history of 6 years of infertility presented to our andrology clinic in Royan institute. In physical examination there was not any palpable vas deferens bilaterally, also The semen analysis was azoospermia. In sonographic evaluation, LT kidney wasn’t seen in its anatomic location. The patient candidate for diagnostic PESA and bilateral PESA were negative. After that, the patient candidate for bilateral TESE and fascinatingly TESE was negative too. After genetic evaluation microdeletion was detected in AZFc subregion of Y chromosome. Conclusion: In men with obstructive azoospermia mostly testicular spermatogenesis is normal but this is not the rule because seldom spermatogenic dysfunction maybe present like our patient. We emphasize about the importance of consideration of obstructive and nonobstructive azoospermia together in a patient for urologists.